Alternative Education Settings in the United States. (November 2020) - Kumm, Skip; Wilkinson, Sarah; McDaniel, Sara
Students with emotional and behavioral disorders who display disruptive behaviors in general education settings are increasingly being educated in alternative education settings. Alternative education settings can vary widely, but they typically have smaller classroom sizes and educational staff who are trained to teach students who were not successful in their previous educational settings. This Current Topics column provides (a) an introduction to how students are placed in those settings, (b) a description of common alternative educational settings, and (c) an overview of effective educational, behavioral, and mental health services available to children and youth in alternative educational settings.